Mexican mathematicians abroad : recent contributions : First Workshop Matemáticos Mexicanos Jóvenes en el Mundo, August 22-24, 2012, Centro de Investigación en Matemáticas, A.C., Guanajuato, Mexico - Matemáticos Mexicanos Jóvenes en el Mundo (Taller de Vinculación); Bárcenas, Noé; Galaz-García, Fernando; Moreno Rocha, Mónica (Aportaciones matematicas / Sociedad Matematica Mexicana, 2016)
This volume contains the proceedings of the First Workshop ``Matematicos Mexicanos Jovenes en el Mundo'', held from August 22-24, 2012, at Centro de Investigacion en Matematicas (CIMAT) in Guanajuato, Mexico. One of the main goals of this meeting was to present different research directions being pursued by young Mexican mathematicians based in other countries, such as Brazil, Canada, Colombia, Estonia, Germany, Spain and the United States, showcasing research lines currently underrepresented in Mexico. Featured are survey and research articles in six areas: algebra, analysis, applied mathematics, geometry, probability and topology. Their topics range from current developments related to well-known open problems to novel interactions between pure mathematics and computer science. Most of the articles provide a panoramic view of the fields and problems the authors work on, making the book accessible to advanced graduate students and researchers in mathematics from different fields. This book is published in cooperation with Sociedad Matematica Mexicana.